A surface model using the eccentric shell and multi-point constraint for warpage prediction of plastics. Issue 2 (20th April 2015) - Zhang, Shi; Zhang, Yun; Shi, Songxin; Huang, Zhigao; Zhou, Huamin
Abstract : Purpose: – The purpose of this paper is to propose a new surface model combining the eccentric shell with multi-point constraint (MPC) for warpage prediction of injection molded plastics. Design/methodology/approach: – In this paper, three benchmark tests and a practical example are implemented to evaluate the performance of the new surface model and existing models. Findings: – The results demonstrate that the proposed model could give satisfactory solutions and has advantages over the existing models. Practical implications: – More precisely predicted warpage field for injection molded plastics can be achieved with the purposed model, such as that in the practical case. Originality/value: – The surface models are efficient and still popular for practical injection molding analysis. However, the existing models for warpage prediction cannot properly represent the true strain energy and obey material continuity assumption, and also they have not been assessed rigorously by benchmark tests. To overcome above-mentioned difficulty, a new surface model is proposed, which employs the eccentric shell without shear factor and MPC equation that ensuring material continuity. The results from experiment illustrate that the new model is superior to existing models.